The SAGE handbook of industrial, work and organizational psychology - Ones, Deniz S., active 2018; Anderson, Neil, active 2018; Sinangil, Handan Kepir; Viswesvaran, Chockalingam (London : SAGE Publications Ltd, 2018)
The third volume in The SAGE Handbook of Industrial, Organizational and Work Psychology concentrates on the broader context of IWO psychology and the many factors influencing the adoption and implementation of IWO practices. Chapter topics include perspectives on IWO psychology around the world, organizational and societal considerations. Chapters have been arranged around 8 key themes: Part 1: Overview Part 2: Professional Context: History Part 3: Organizational Capabilities and Context Part 4: Strategic Management Part 5: Triple Bottom Line Part 6: Diversity and Cross-Cultural Issues Part 7: Stress, Safety & Health Part 8: Managing Careers and Work Life Volume III offers a comprehensive overview of the field for anyone working in or studying managerial or organizational psychology.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Psychology, Industrial -- Handbooks, manuals, etc